HUBUNGAN MINAT DAN KEMANDIRIAN BELAJAR DENGAN PENGUASAAN KONSEP MATERI PADA SISWA SMK SANTA MONIKA KUBU RAYA - Gedion yarso; Herkulana Herkulana; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis thesis is entitled "The Relationship between Interest and Learning Independence With Mastery of the Concept of Inventory Materials of Trading Companies in Class XI Students at SMK Santa Monika Kubu Raya". The method used is descriptive in the form of correlational research. Sources of data in this study were all students of class XI majoring in accounting at SMK Santa Monika. The results of the study 1) There is a positive and significant correlation between variables (X1) and (Y) partially at 0.829. larger than the value of the critique of correlation in the product moment correlation table (α = 0.05) at dk = nk-1 = 67-2-1 = 64 that is 0.254 or (0.829> 0.254. Thus, it can be concluded that there is a very strong relationship between (X1) and (Y) 2) There is a positive and significant correlation between (X2) and (Y) partially of 0.791. larger than the value of the correlation critique in the product moment correlation table (α = 0.05) at dk = n-k-1 = 67-2-1 = 64 which is 0.254 or (0.791> 0.254). Thus it can be concluded that there is a very strong relationship between (X2) with (Y) 3) There is a positive and significant correlation directly from the variables (X1) and (X2) simultaneously (Y), the magnitude of the correlation is 833. Larger compared with the value of the correlation critique in the product moment correlation table (α = 0.05) at dk = nk-1 = 67-2-1 = 64 that is 0.254 or (0.833> 0.254). Thus it can be concluded that there is a very strong relationship between (X1) and (X2) simultaneously (Y). Keywords: Learning Interest, Independence, Concept Mastery